Visible-light photocatalytic O2-to-H2O2 via nitrogen-graphene quantum dots-modified Bi2Fe4O9 for synchronizing the reduction of Cr(VI) and oxidation of organic contaminants: Kinetics, mechanism, and performance - Wei, Ling-Wei; Zheng, Meng-Wei; Liu, Shou-Heng; Paul Wang, Hong; Pu, Ying-Chih; Nguyen, Van-Can (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •N-GQDs/Bi2Fe4O9 suppress charge recombination and electron accumulation.•N-GQDs/Bi2Fe4O9 enhances in-situ H2O2 generation and H2O2 activation.•Electrons accumulation around N-GQDs accelerate the redox cycles of Fe(II)/Fe(III).•N-GQDs/Bi2Fe4O9 achieves simultaneous toxic Cr(VI) reduction and BPA oxidation in wastewater.•N-GQDs/Bi2Fe4O9 enables energy self-sufficient and simplified wastewater treatment methods. Synergistic coexistence of toxic chromium and organic contaminants in wastewater has made treatments highly complicated. As solar-driven wastewater treatments become increasingly environmentally and economically attractive, a photocatalyst (denoted as N-GQDs/Bi2Fe4O9) is developed for photocatalytic reduction of Cr(VI) and simultaneous oxidation of organic contaminants in wastewater. Incorporating N-GQDs (as electron reservoir) into Bi2Fe4O9 modulates the band structure (from 2.40 to 2.24 eV), facilitating charge transfer and electron accumulation at N-GQDs. Due to the photo-Fenton synergistic reaction between N-GQDs/Bi2Fe4O9 photocatalysis process, N-GQDs/ Bi2Fe4O9 demonstrates excellent H2O2 generation (1.64 μM min−1) and H2O2 activation (0.0063 min−1) performance, leading to generation of more highly reactive species (i.e., OH radicals), achieving BPA removal of 99.9 % under visible-light irradiation for 100 min. Interestingly, the photo-Fenton synergistic reaction enhances the reduction of Cr(VI) (99.8 %), while the Fe(II) active sites on the N-GQDs/Bi2Fe4O9 can also promote the synchronized Cr(VI) reduction. Also, the accumulated electron around N-GQDs enhances redox cycles of Fe(II)/Fe(III) reactions to realize the sustainable photo-Fenton catalytic reaction. This new N-GQDs/Bi2Fe4O9 photocatalyst demonstrates the feasibility of concurrent reduction of toxic Cr(VI)-to-Cr(III) and oxidation of organic contaminants in wastewater with a simple process via nearly unlimited solar energy.